2023
DOI: 10.3390/buildings13102426
|View full text |Cite
|
Sign up to set email alerts
|

Validation of One Predominant Frequency Presence in Seismic Ground Displacement by Means of Deformation Response Spectra

Cesar A. Morales

Abstract: There are very few results in the literature on spectral content of seismic ground displacement; nonetheless, these results are singular as most of the spectral content is limited to a very narrow low frequency band, contrary to ground acceleration. These few spectral characterizations have been obtained, expectedly, by means of power spectral or Fourier analyses of ground displacement records, only. As these records are not as reliable as ground acceleration records, the existence of a clear predominant frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Indeed, in the middle of Table 1, which is in chr order, we have the Chi Chi and Hector M. events which were recorded digitall inantly [9]. In fact, the low-cut frequency reached 0.02 Hz for Hector M. seism [10]. Moreover, for the later (in Table 1) Latin American events, including Sierr the cutoff frequency was around 0.03 Hz [6].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Indeed, in the middle of Table 1, which is in chr order, we have the Chi Chi and Hector M. events which were recorded digitall inantly [9]. In fact, the low-cut frequency reached 0.02 Hz for Hector M. seism [10]. Moreover, for the later (in Table 1) Latin American events, including Sierr the cutoff frequency was around 0.03 Hz [6].…”
Section: Resultsmentioning
confidence: 94%
“…The hypothesis of this research is that clear resonant frequencies will be observed because neat predominant frequencies exist in Fourier or power spectra of ground displacement [5,6]. A theoretical basis for this, based on a generalized transmissibility concept, has been given by Morales recently (2023) [10]. Therefore, deformation response spectrum plots will be constructed, and an evident and clean predominant frequency will be observed, as shown in Figure 1, where peak response displacement (PRD) is plotted against natural frequency (instead of natural period, which is the other option).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations